2020
DOI: 10.2478/bog-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the use of motorcycles and the level of development of countries?

Abstract: Our paper aims to analyse the hypothesis that locations with a higher Human Development Index (HDI) present lower rates of motorcycle use. For this we use an econometric model for 117 countries on five continents for the years 2013, 2015 and 2018. We assume that when a country reaches a higher level of development, its population is more likely to experience improvements in the quality of life, which also affects the quality of individual transportation, public transport and roads. Increases in income discoura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…The increased death rates were related to the increased motorized 2–3 wheelers in our study which was supported by others [ 14 , 20 , 21 ]. The use of motorized 2–3 wheelers increase the chances of getting a job in poor countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased death rates were related to the increased motorized 2–3 wheelers in our study which was supported by others [ 14 , 20 , 21 ]. The use of motorized 2–3 wheelers increase the chances of getting a job in poor countries.…”
Section: Discussionsupporting
confidence: 91%
“…This ratio declines later on when the GNI increases more. Cars will be preferred at this stage because they are safer and more comfortable [ 6 , 21 , 28 30 ]. The increased GNI is also related to the effective implementation of road safety regulations (including helmet law), and improvement in medical care [ 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas heterogeneity of traffic is not considered, few studies incorporate different vehicle classes to evaluate speed differentials on horizontal alignment [39]. Developing countries, such as Malaysia, have higher motorcycle ownership and dependency rates than developed countries because of their lower socioeconomic status [40]. Several studies have found significant speed differences between passenger cars and heavy vehicles while traversing tangent to curve sections [41].…”
Section: Related Studiesmentioning
confidence: 99%
“…These vehicles offer numerous advantages, including their small size, which makes them easier to park, and their low maintenance and insurance costs. In contrast, motorcycles in developed countries are often more advanced (with higher cylinder engines), generally do not carry passengers, and are mostly used for recreational purposes, such as extreme sports and road trips [3]. Typically, the higher the human development index of a country, the lower the usage of motorcycles, although this relationship is not strictly linear [3,4].…”
Section: Introductionmentioning
confidence: 99%